The chocolate falcon fraud [large type] : a chocoholic mystery - Carl, JoAnna (Carl, JoAnna. Chocoholic mystery., 2016)
The Warner Pier tourism board is kicking off its Tough Guys and Private Eyes film festival with The Maltese Falcon, and Lee Woodyard and her Aunt Nettie are preparing a delicious chocolate noir tie-in at TenHuis Chocolade. What Lee isn't prepared for is a face from the past: Jeff Godfrey, her former stepson. The last time Jeff showed up in town, he wound up being accused of murder. Now he says he's only in Warner Pier to see Bogart on the big screen. Honest. Jeff may now be a college grad, but that doesn't mean he's any less naíve than the kid Lee had to bail out of trouble earlier. There are all those strange phone calls, a girlfriend who's secretly on Jeff's tail, and a pack of suspicious-sounding acquaintances right out of Dashiell Hammett. Then Jeff goes missing, the Falcon theme is haunting everyone, and a body falls at Lee's feet when she opens the front door just like in the movie. Now Lee is under deadline to rewrite the ending of a cunning killer's increasingly convincing murder plot.